ROYALTI SEBAGAI DASAR UNTUK REVOLUSI MUSIK Indonesia - Hestiandari, RR. Ella Evrita (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2022)
Along with the growing era, the industrial world is also experiencing revolutionary changes that bring its own advantages and challenges. In line with this, several aspects related to intellectual property are also slowly starting to develop. To overcome the occurrence of copyright infringement, the government has issued regulations regarding the management of copyright royalties for songs and music in PP No. 56 of 2021 concerning Royalty Management. The method used in this research is a literature review which consists of a sequence of actions related to library data collection, reading and taking notes, and organizing research materials. All forms of copyright get a legal protection that has been stated in the applicable Copyright Law. Along with the development of the era, music industry players must be good at using new media in publishing their work to the audience. So that through the uploaded works, monetizing can be done.